Comparing Social Isolation in Older Adults With and Without Physical Health Challenges During COVID-19: Church and Church Friends Matter - Tina R. Kilaberia PhD, MSW; Yuanyuan Hu PhD, MSW; Edward R. Ratner MD; Janice F. Bell PhD, MPH, MN (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Older adults were disproportionately affected by COVID-19. The purpose of this study was to explore experiences of sudden-onset social isolation and factors that influenced it among older adults. A qualitative thematic study with a survey component was conducted comparing 18 older adults in two groups: 12 reporting physical health challenges and 6 reporting no physical health challenges. Three qualitative themes describe experiences of (a) avoiding risk to personal health as the reason to postpone healthcare, (b) grieving church and church friends as a lost social connection, and (c) compound stress due to converging factors related to personal health, public health, racial justice movement and critical national events. Those with physical health challenges were less able to postpone seeking healthcare, suffered from compound stress, and were more likely to feel isolated when unable to participate in church activities. Religious, faith, or spiritual supports may be important buffers against social isolation during public health emergencies, especially for older adults with physical health challenges and when there is concurrent social unrest.